Development of the generic, multidimensional Treatment Expectation Questionnaire (TEX-Q) through systematic literature review, expert surveys and qualitative interviews - Bernd Löwe; Yvonne Nestoriuc; Jannis Alberts; Maja Alicia Glahn; Keith Petrie; Johannes Laferton; Meike Shedden-Mora (BMJ Open)
Objective Patients’ expectations—as a central mechanism of placebo and nocebo effects—are an important predictor of health outcomes. However, the lack of a way to assess expectations across different settings restricts progress in understanding the role of expectations and to quantify their importance in medical and psychological treatments. The aim of this study was to develop a theory-based, generic, multidimensional measure assessing patient expectations of medical and psychological treatments.Design The Treatment Expectation Questionnaire (TEX-Q) was developed based on the integrative model of expectations and a systematic literature review of treatment expectation scales. After creating a comprehensive item pool, the scale was further refined by use of expert ratings and patient interviews.Setting Patients were recruited in primary care at two hospitals in Hamburg, Germany.Participants 13 scientific experts participated in the expert survey. 11 patients waiting for psychological or surgical treatments participated in the qualitative interviews.Results The 2×2×2 multidimensional structure of the TEX-Q assesses two expectation constructs (probabilistic vs value-based) across two outcome domains with two valences (direct benefits and adverse events, broader positive and negative impact), plus process and behavioural control expectations. We examined 583 items from 38 scales identified in the systematic review and developed 78 initial items. Content validity was then rated by experts according to item fit and comprehensibility. The best 53 items were further evaluated for comprehensibility, acceptability, phrasing preference and understanding by interviewing patients prior to treatment using the ‘think aloud’ technique. This resulted in a first 35-item version of the TEX-Q.Conclusions The TEX-Q is a generic, multidimensional measure to assess patient expectations of medical and psychological treatments and allows comparison of the impact of multidimensional expectations across different conditions. The final TEX-Q will be available after psychometric validation.